Monoclonal B-cell lymphocytosis in individuals from sporadic (non-familial) chronic lymphocytic leukemia families persists over time, but does not progress to chronic B-cell lymphoproliferative diseases - Matos,Daniel Mazza (2015)
BACKGROUND: Monoclonal B-cell lymphocytosis is classified as 'high-count or clinical' monoclonal B-cell lymphocytosis and 'low-count or population' monoclonal B-cell lymphocytosis. Previously, 167 first-degree relatives pertaining to sporadic (non-familial) chronic lymphocytic leukemia families were studied and the presence of seven monoclonal B-cell lymphocytosis individuals was reported.OBJECTIVE: The aim of this report is to describe the outcomes of five of the original monoclonal B-cell lymphocytosis individuals.METHODS: Flow cytometry analysis was performed on mononuclear cells previously isolated from peripheral blood samples. A strategy of sequential gating designed to identify the population of CD19+/CD5+ B-lymphocytes was used and, subsequently, the monoclonal B-cell lymphocytosis cells were characterized by the CD20weak/CD79bweak/negative phenotype.RESULTS: The monoclonal B-cell lymphocytosis clone showed consistent stability over time with little variations in size. After a median follow-up of 7.6 years, none of the five monoclonal B-cell lymphocytosis individuals progressed to chronic lymphocytic leukemia or other B-cell lymphoproliferative disease.CONCLUSIONS: The data of this study suggest that chronic lymphocytic leukemia-like monoclonal B-cell lymphocytosis detected in the context of sporadic chronic lymphocytic leukemia families is not prone to clinical evolution and could be just a sign of immune senescence.